Oxidation and adsorption of gas-phase Hg0 over a V2O5/AC catalyst. Issue 81 (16th August 2016) - Wang, Jun-Wei; Shen, Yuan-Yuan; Dong, Yan-Jie; Qin, Wei; Zhang, Qing-Ping; Lu, Lu; Zhang, Yuan-Guang
Abstract : V2 O5 /AC had a high Hg 0 capture capability due to the co-effects of oxidation and adsorption and O2 enhanced Hg 0 oxidation. Abstract : Oxidation and adsorption of gas-phase Hg 0 over a V2 O5 /AC catalyst was studied in N2 and N2 + O2 atmospheres. The results showed that the V2 O5 /AC catalyst had a high Hg 0 capture capability in N2 and N2 + O2, which can be attributed to the critical role of V2 O5 oxidation activity for oxidizing Hg 0 to Hg 2+ (form HgO). O2 promoted Hg 0 oxidation and its role was mainly to resume the oxidation activity of V2 O5 by replenishing O to the used V2 O5 sites. It was found that only a portion of the V2 O5 sites on the V2 O5 /AC surface were effective for Hg 0 oxidation. The high Hg 0 capture capability of V2 O5 /AC was due to the combined effects of oxidation and adsorption, and the effect extent of each was different at different temperatures.